La via francese alla limitazione delle libertà e il dialogo con le religioni al tempo del coronavirus (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Cenni introduttivi - 2. Le limitazioni normative alle libertà personali - 3. Il dialogo e la collaborazione delle autorità statali con le autorità religiose e morali del Paese - 4. La libertà religiosa tra preparazione e prima attuazione della fase del cosiddetto deconfinamento - 5. La decisione del Conseil d’État e il successivo intervento governativo - 6. Il graduale ritorno alla “normalità”. Brevi conclusioni interlocutorie.The French way to the restriction of freedoms and the dialogue with religions at the time of the coronavirusABSTRACT: The essay focuses on the French legal system at the time of the Coronavirus and the analysis of two different profiles, even if they are intimately related to each other. The first involves the analysis of the legal mechanisms through which the State has achieved the restriction of personal freedoms, including religious freedom. The second, instead, essentially concerns the analysis of the relations maintained, in this circumstance, by the State institutions, with the different religious groups and conversely.